Female Teacher Workload, Problem, and Social Competence: A Study on Secondary School Teachers - Suswati Hendriani; Rahmawati Rahmawati; Deswita Deswita; Khairina Khairina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Heavy workload has become a problem of many female teachers in the world. Finding out how workload has impacted teachers’ job effectiveness worth searching. The respondents of the research were were 78 secondary school female teachers in Tanah Datar Regency. The data of the research were collected through a google-form. The data were analyzed through Descriptive Statistics. The study results show that female teachers are over-burdened with their tasks at school and at home, face many problems like having negative feeling to themselves, having no leisure time, lacking of social responsibility and participation in school activities and house work, being not optimal in job performance, being exhausted, feeling lack of energy, getting problem in time management, doing social withdrawal, and having lower social competence after the issuance of the new regulation. Therefore, it is recommended that the new government regulation of teacher workload be quitted in order that better education quality is achieved.